Implementation of information technology in a South African construction company: A case study. Issue 1 (2014) - Eicker, Albert; Weeks, Richard
Abstract The unpacking and uptake of technologies and specifically information technology has proven to be a critical strategic tool in many industries, but considering the nature of the construction industry this adoption of new technologies have been relatively slow in comparison (Kim, 2003:25). This research study investigates the technology information implementation strategies and methodologies followed by an industry representative of the construction industry. The main theoretical proposition of the study is to understand the factors that influence technology systems implementation projects at construction organisations and to establish the rational for those influencing factors. The contextual comparison between the approaches followed by the company and of that reported in relevant implementation derived literature highlights the evident disparities and explores the results thereof. The findings revealed that the underlying cause of the implementation problems were in the fact that the technology and overall company strategies where misaligned and that the user requirements for the implementation project were not clearly defined from the onset of the project. Organisational culture and leadership primarily dictates the direction of implementation projects, and the identification and selection of technologies are conducted in an isolated fashion, further driving the internal misalignment between departments and strategies. For future technology implementation projects it is proposed that clear user requirements are established and that thorough change management programmes are utilised to ensure stakeholder buy‐in throughout the organisation, this would also drive the alignment of the different internal business strategies within the organisation.